If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1u + -9 = -2u Reorder the terms: -9 + -1u = -2u Solving -9 + -1u = -2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2u' to each side of the equation. -9 + -1u + 2u = -2u + 2u Combine like terms: -1u + 2u = 1u -9 + 1u = -2u + 2u Combine like terms: -2u + 2u = 0 -9 + 1u = 0 Add '9' to each side of the equation. -9 + 9 + 1u = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 1u = 0 + 9 1u = 0 + 9 Combine like terms: 0 + 9 = 9 1u = 9 Divide each side by '1'. u = 9 Simplifying u = 9
| 10x-15=13x-20 | | 3(3x+9)=11x-3 | | 3y=-9+2y | | X^2-3x+2k=0 | | 13x+10=15x-16 | | -2x-3(4+5x)=-63 | | 25x^2-100x+100= | | 6m+10=8m | | 7x+4(-3x)(-12)=8 | | -10k+20=13k-18-8 | | 16(6x-24)=x-4 | | 11x-5=6x+25 | | 3g+3W=300 | | 24-4x=3(x+1) | | 65=5(4x+1) | | 7p-4+12p=-15+3p | | 8w+4=8w | | 8x^2-4x= | | P=2-2q | | 52=w-8 | | -11+9t=11-4t+17 | | 3y+y+20=7y+20-5y | | 4K-23=-5(7k-11) | | 4(3-x)+5(x-6)=x | | 6p-5+7p=47 | | 6a-3(a+2)=1/2(a+8) | | 16p-4=-15 | | 4K-23=-5(7k+11) | | 2c+(3c-4)=5c-4 | | -2w-18w-9=-18w+5 | | 7c-4=31 | | 18-6a=-1a-12 |